Combination of trio-based whole exome sequencing and optical genome mapping reveals a cryptic balanced translocation that causes unbalanced chromosomal rearrangements in a family with multiple anomalies - Xie, Min; Xue, Jiangyang; Zhang, Yuxin; Zhou, Ying; Yu, Qi; Li, Haibo; Li, Qiong (Frontiers in Genetics, 2023)
Background: Balanced translocation (BT) carriers can produce imbalanced gametes and experience recurrent spontaneous abortions (RSAs) and even give birth to a child with complex chromosomal disorders. Here, we report a cryptic BT, t(5;6)(p15.31;p25.1), in the proband’s grandmother, which caused unbalanced chromosomal rearrangements and various anomalies in the two subsequent generations. We also provide a thorough overview of the application of optical genome mapping (OGM) to identify chromosomal structural variants (SVs). Methods: Trio-based whole exome sequencing (Trio-WES) was conducted to explore the genetic basis of the phenotype of the proband and her mother. High-resolution karyotype analysis and OGM detection were performed on the proband’s grandparents to trace the origin of the unbalanced rearrangements between chromosomes 5 and 6. A PubMed search was conducted with the following keywords: “OGM” and “SVs”. Then, relevant studies were collected and systematically reviewed. Results: The proband and her mother presented with various anomalies, whereas the grandmother was healthy but had a history of four abnormal pregnancies. Trio-WES revealed a heterozygous duplication on the terminal region of chromosome 5p and a heterozygous deletion on the proximal end of chromosome 6p in the proband and her mother. High-resolution karyotype analysis revealed no aberrant karyotypes in either grandparent, whereas OGM detection revealed a cryptic BT, t(5;6)(p15.31;p25.1), in the proband’s grandmother. An overwhelming majority of research publications have verified the clinical utility of OGM in detecting SVs. Conclusion: The results of this study revealed that the unbalanced chromosomal rearrangements and many anomalies observed in multiple members of the family were attributable to the cryptic BT carried by the proband’s grandmother. This study supports that OGM has a unique advantage for detecting cryptic BTs, and can be used as a first-tier genetic test for the etiological diagnosis of infertility, RSAs, and other complex genetic disorders.